PENGARUH BRAND AMBASSADOR, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN NIKE - Ghivari Varreldiazka; Nobelson Syarief; Yudi Nur Supriadi (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to determine and analyze the effect of brand ambassador, product quality, and price on Nike basketball shoes purchase decision in South Jakarta. This research is using quantitative method with 75 respondents in South Jakarta with purposive sampling technique. The data analysis technique was taken through a questionnaire with descriptive data analysis techniques then tested the validity and reliability test and then continued with hypothesis testing using SmartPLS 3.0. Hypothesis testing in this study used the analysis of the inner model, outer model, and t-statistical test and significance level of 5% (0.05). The result shows that (1) brand ambassador variable has an effect of 0.186 positive and significant effect on purchase decision, (2) product quality has an effect of 0.665 positive and significant effect on purchase decision, (3) price has an effect of 0.143 positive and significant effect on purchase decision. While the contribution that was given by the variable of brand ambassador, product quality, and price collectively is 0.960 or 96%